Dantrolene e células-tronco mensenquimais no tratamento do trauma medular agudo em ratos Wistar - Bruno Benetti Junta Torres (2014)
This study aimed to evaluate the effects of dantrolene (DAN) and mesenchymal stem cells (MSCs) in acute spinal cord injury (SCI). Sixty three-months-old male Wistar rats were divided into groups MSCs, MSCs + DAN, DAN, positive control (PC) (trauma and placebo) and negative control (NC) (no trauma and placebo). Laminectomy was performed at T12 level in all animals, followed by a weight-drop model of SCI, except for the NC group. An hour later, the MSCs + DAN and DAN groups received 10mg/kg of DAN in a single dose, intraperitoneally, and after seven days, the MSCs and MSCs + DAN groups received 1x106 cells intravenously. Functional recovery was assessed through BBB and adapted descriptive scale methods for 30 days. Spinal cord was evaluated with H.E., immunoistochemistry with anti-NeuN, and real time RTPCR to assess gene expression of neurotrophic factors (BDNF and NT-3), antiapoptotic (Bcl-2 and Bcl-xl) and pro-apoptotic proteins (caspase-3, caspase-9 and Bax), in the cranial and caudal segments from the lesion epicenter. Traumatized animals showed severe paraplegia and urinary retention with hemorrhagic cystitis. There was a significant recovery in groups MSCs, DAN and MSCs + DAN (p<0.05) compared to PC. Histologically, there was no systemic changes. It was observed severe spinal injury, characterized by axonal degeneration and neuronal loss, which extended cranio-caudally from epicenter. All groups showed average number of NeuN-positive neurons significantly higher when compared to PC (p<0.05). The SCI resulted in reduced BDNF, NT-3 and Bcl-xl gene expression, and increased Bax and caspase-3 expression. After treatments, there was a significant increase in BDNF expression in MSCs, MSCs + DAN and DAN groups compared to PC group (p<0.05). The NT-3 expression was higher in MSCs + DAN and DAN groups in cranial segments (p<0.05), and DAN group in the caudal ones (p<0.01). The Bax expression was significantly lower in the MSCs + DAN (p<0.05) and DAN (p<0.001). The caspase-3 and 9 expression were significantly lower in DAN, MSCs and MSCs + DAN groups (p<0.05). It was concluded that DAN, MSCs or the combination of both for the treatment of SCI in rats promote functional recovery and neuroprotection through neurotrophic and antiapoptotic effects.